Optimized biodegradation of carcinogenic fungicide Carbendazim by Bacillus licheniformis JTC-3 from agro-effluent. Issue 1 (January 2018) - Panda, Jigisha; Kanjilal, Tiyasha; Das, Sumona
Abstract: The aim of this research work is to study biodegradation of Carbendazim, a globally used carcinogenic fungicide, by novel bacterial strain Bacillus licheniformis JTC-3, isolated from local agro-effluent, as it wrecks havoc on human immune, nervous and endocrine systems, upon consumption. The strain was characterized by various biochemical tests, antibiotic assay and identified by 16S rDNA analysis. High Performance Liquid Chromatographic studies showed its biodegradation capacity to be very high (73.2% of initial Carbendazim concentration), in Minimal Salt Media, within 24 h of incubation. Various growth parameters (temperature, agitation speed, pH, substrate concentration) were optimized by Central Composite Design to get the biodegradation rate of 0.305 mg/L of Carbendazim/h/mg biomass. Scanning Electron Micrograph, X-ray diffraction, Fourier Transform Infra-Red spectroscopic microanalysis and toxicity testing of metabolic end-product confirmed formation of non-toxic, crystalline 2-hydroxybenzimidazole. Accordingly, a plausible mechanism of biodegradation of Carbendazim has been proposed here. The isolate's growth curve and the rate kinetics mathematically fitted well with Gompertz model and second order reaction, respectively.